ChemInform Abstract: Kinetic Resolution of Secondary Alcohols Catalyzed by Chiral Phosphoric Acids. Issue 9 (4th March 2014) - Harada, Shingo; Kuwano, Satoru; Yamaoka, Yousuke; Yamada, Ken‐ichi; Takasu, Kiyosei
Abstract A new electronically tuned binaphthyl‐based phosphoric acid is developed, that, in contrast to conventional methods, allows the kinetic resolution of a broad range of secondary alcohols without the need of stoichiometric amounts of base.